Prototype Sistem Monitoring Volume Bak Sampah Online Berbasis Arduino Nano dan Orange Pi - Mappatoba, Andi; Haruna, Ilham; Agussalim, Agussalim (JITCE (Journal of Information Technology and Computer Engineering), 2020)
This research aims to develop trash volume monitoring based on Arduino nano and orange pi. This prototype detected trash volume in the trash can, and send the information through the monitoring server via a cellular network in real-time. So that the trash management, in this case, Dinas Kebersihan, could be efficient. In which the trash can located in various places could be easily monitored through the website. The results show, optimum range for the sensor that installed in the trash can is maximal 25 cm, in which for every trash that detected by sensor must be in range of 0 cm between 4.5 cm, where the position of the sensor does not face to face so that the sensor detects more accurately in determining the volume of free space in the trash.